2020
DOI: 10.1177/0361198120959076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative Messages and Sign Locations on Driver Response to a Dynamic Speed Feedback Sign on a Freeway Interchange Ramp

Abstract: Research was undertaken to determine effective messaging strategies and sign positions for dynamic speed feedback signs (DSFS) when used for speed management at freeway ramp curves. A field evaluation was performed in this setting to assess the impacts of a DSFS on driver speed selection and braking characteristics while approaching and entering the curve. Three feedback messaging strategies were evaluated at three sign positions in advance of the curve. Compared with the existing site (without the DSFS), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 3 publications
5
17
0
Order By: Relevance
“…It is also worth noting that the DSFS had a similar effect on driver response across all vehicle categories. These results are aligned with prior findings associated with DSFS use in similar freeway ramp settings ( 8 ).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…It is also worth noting that the DSFS had a similar effect on driver response across all vehicle categories. These results are aligned with prior findings associated with DSFS use in similar freeway ramp settings ( 8 ).…”
Section: Resultssupporting
confidence: 89%
“…The DSFS had no significant effect on reducing excessive curve entry speeds or improving brake response at this particular site. These results are consistent with earlier phases of the research at an alternative ramp location, which found the DSFS to be less effective when positioned 400 ft upstream of the curve ( 8 ). One possible reason for the diminishing effectiveness at increasing advance warning distances is that drivers may be more likely to disregard warning messages that are provided too far in advance of a hazard.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations